The Effectiveness of Transdiagnostic Therapy on Anxiety, Depression, Cognitive Strategies of Emotional Regulation, and General Performance in Women with Comorbid Anxiety and Depression - Farzaneh Hooman; Mahnaz Mehrabizadeh Honarmand; Yadolah Zargar; Iran Davodi (Journal of Advanced Biomedical Sciences, 2015)
Background & Objectives: The purpose of the current study was investigation the effectiveness of group transdiagnostic therapy on anxiety, depression, cognitive strategies of emotional regulation, and general performance in women with comorbid anxiety and depression in Ahwaz, Iran.